Corporate Creativity Socialization Program: Preventing Impulsive Buying and Building Habits in Families - Alfin Nur Arifah; Dheri febiyani Lestari; Rizky Ridwan; Aditia Abdurachman; Rina Madyasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The "Entrepreneurship Socialization: Preventing Impulsive Buying and Cultivating Saving Habits in Families" program in Cikeusal Village, Tanjung Jaya Subdistrict, is a proactive initiative aimed at stimulating local economic growth and enhancing financial literacy at the household level. The program addresses real challenges in the form of detrimental impulsive buying and a lack of savings habits within rural communities. The main focus of the program is to transform consumption patterns by integrating creativity and entrepreneurship as the main pillars. Through a series of training sessions, and socialization activities, we provide an in-depth understanding of local business potential and empower the residents of Cikeusal Village to develop their entrepreneurial skills. Preventing impulsive buying is another objective of this program, where intensive education is provided on its negative impacts and strategies for managing consumer temptations. The program also emphasizes the establishment of saving habits as a foundation for strong family finances. Through a participatory approach, the program has successfully instigated positive behavioral changes in the community of Cikeusal Village. By embracing creativity as an economic resource, preventing impulsive buying behavior, and encouraging saving habits, this program aims to have a long-term impact on building economic resilience and family well-being at the village level. The success and challenges of the program are revealed through quantitative and qualitative data analysis, providing a holistic view of the impact and directions for further development.